1998
DOI: 10.1007/bf02467456
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cortisol in plasma and urine by thin-layer chromatography and fluorescence derivatization with isonicotinic acid hydrazide

Abstract: Key WordsThin-layer chromatography Cortisol Isonicotinic acid hydrazide Plasma and urine SummaryA simple, inexpensive and reliable method is described for the measurement of cortisol in guinea-pig plasma and urine by thin-layer chromatography (TLC) and densitometry. Plasma and urine were extracted with dichloromethane and the extracts chromatographed on aluminium-backed silica gel TLC plates with concentrating zones. The plates were then dipped into the isonicotinic acid hydrazide (INH) reagent (3 g INH, 5 g t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The linear relationship of increasing amounts of cortisol and cortisone and INH-derived fluorescence is summarised in Figure 6. In agreement with previous work [9,10] fluorescence intensity of isonicotinyl hydrazones was significantly increased by dipping the chromatograms into paraffin/chloroform (1:2, v/v) and scanning them 10 min after the last dipping. The sensitivity was 12ng spot 1 for cortisol and 16ngspot 1 for cortisone (INH, without dipping into paraffin/chloroform) and 3 ng spot 1 for cortisol and 6 ng spot 1 for cortisone (INH, with dipping into paraffin/chloroform).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The linear relationship of increasing amounts of cortisol and cortisone and INH-derived fluorescence is summarised in Figure 6. In agreement with previous work [9,10] fluorescence intensity of isonicotinyl hydrazones was significantly increased by dipping the chromatograms into paraffin/chloroform (1:2, v/v) and scanning them 10 min after the last dipping. The sensitivity was 12ng spot 1 for cortisol and 16ngspot 1 for cortisone (INH, without dipping into paraffin/chloroform) and 3 ng spot 1 for cortisol and 6 ng spot 1 for cortisone (INH, with dipping into paraffin/chloroform).…”
Section: Resultssupporting
confidence: 91%
“…Both steroids were well separated from the bulk of other lipophilic substances which ascended 1 25mm note that the width of the concentrating zone ( furthermore shows the presence of a nonsteroidal compound in urinary chromatograms (Rv = 0.27) that appears to be caffeine because of the same mobility as authentic caffeine in seven different solvent systems, because of the same spectral absorbance curve as authentic caffeine, and because of the linear correlation of caffeine amount ingested in-vivo and its amounts excreted in timed urinary specimens. When plates were dipped into the INH reagent, isonicotinyl hydrazones of cortisol and cortisone formed within 1 h [9]. On the other hand caffeine did not react with INH, thus its presence did not interfere with the determination of steroids ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RIA in general has high sensitivity but often lack selectivity due to cross-reactivity with related substances [10,11]. To improve selectivity, Takao et al [12] and Fenske [13] reported methods based on derivatization of cortisol with a fluorescent reagent, followed by HPLC or thin-layer chromatography, respectively. LC coupled with mass spectrometry (MS) or tandem MS/MS is a powerful and selective technique that has been used to determine steroid hormone levels [14][15][16]; however, most of the reported assays used d-4 cortisol as internal standard (IS), which may not be readily available [15,16].…”
Section: Introductionmentioning
confidence: 99%